Platelet-Derived Growth Factor CC-Mediated Neuroprotection against HIV Tat Involves TRPC-Mediated Inactivation of GSK 3beta - Peng, Fuwang (Public Library of Science, 2012)
Platelet-derived growth factor-CC (PDGF-CC) is the third member of the PDGF family, and has been implicated both in embryogenesis and development of the CNS. The biological function of this isoform however, remains largely unexplored in the context of HIV-associated dementia (HAD). In the present study, we demonstrate that exposure of human neuroblastoma cells SH-SY5Y to HIV transactivator protein Tat resulted in decreased intrinsic expression of PDGF-CC as evidenced by RT-PCR and western blot assays. Reciprocally, pretreatment of SH-SY5Y cells with PDGF-CC abrogated Tat-mediated neurotoxicity by mitigating apoptosis and neurite & MAP-2 loss. Using pharmacological and loss of function approaches we identified the role of phosphatidylinositol 3-kinase (PI3K)/Akt signaling in PDGF-CC-mediated neuroprotection. We report herein a novel role about the involvement of transient receptor potential canonical (TRPC) channel 1 in modulation of calcium transients in PDGF-CC-mediated neuroprotection. Furthermore we also demonstrated PDGF-CC-mediated inactivation of the downstream mediator - glycogen synthase kinase 3β (GSK3β) evidenced by its phosphorylation at Ser-9. This was further validated by gain and loss of function studies using cells transfected with either the wild type or mutant GSK3β constructs. Intriguingly, pretreatment of cells with either the PI3K inhibitor or TRPC blocker resulted in failure of PDGF-CC to inactivate GSK3β, thereby suggesting the intersection of PI3K and TRPC signaling at GSK3β. Taken together our findings lead to the suggestion that PDGF-CC could be developed as a therapeutic target to reverse Tat-mediated neurotoxicity with implications for HAD.